Status of Torch Infections in Women of Child Bearing Age Group in Uttar Pradesh - Neha T., Shahi; T.N., Dhole; P.L., Sankhwar (International Journal of Innovative Research in Medical Science, 2017)
Purpose: The present study was conducted to estimate the seroprevalence of Toxoplasma, Rubella, Cytomegalovirus, Herpes Simplex Virus (TORCH) infections among the pregnant females of <22 weeks of period of gestation with Bad Obstetric History(BOH) in Uttar Pradesh. Material & Method: Over a period of one year, 100 patients blood samples were collected after screening of 2000 pregnant females of <22 weeks of period of gestation having BOH. Serum was separated from blood by centrifugation. All samples were examined by ELISA for the presence of TORCH antibodies IgM and IgG. Results: Out of the 100 blood samples screened, 75 (75%) cases were seropositive for (TORCH) Toxoplasma, Rubella, CMV and HSV alone or in combination. Out of 75 seropositive cases, 44 (58.66%) were positive for any one of the components (Toxoplasma, Rubella, Cytomegalovirus or Herpes simplex virus), 20 (26.67%) were positive for any two components (Toxoplasma with Rubella, Toxoplasma with Cytomegalovirus, Toxoplasma with Herpes simplex virus, Rubella with Cytomegalovirus, Rubella with Herpes simplex virus or Cytomegalovirus with Herpes simplex virus). 9 (12%) cases were positive for any three components (Toxoplasma with Rubella & Cytomegalovirus, Toxoplasma with Rubella & Herpes simplex virus, Toxoplasma with Cytomegalovirus & Herpes simplex virus, Rubella with Cytomegalovirus & Herpes simplex virus. Whereas 2 (2.67%) cases were positive for all four components of TORCH (Toxoplasma, Rubella, Cytomegalovirus & Herpes simplex virus). Among 44 cases which were positive for any one component of TORCH, there was Toxoplasma in 3 cases (6.81%), Rubella in 2 cases (4.55%), CMV in 20 cases (45.45%) and HSV in 19 cases (43.19%). IgM positivity for Toxoplasma was 16.67%, for Rubella was 7.14%, for CMV was 68.75% and for HSV were 2.22% of their respective values. Conclusion: This study shows that there is a very strong association of TORCH agents as a potential cause of BOH. Hence screening and early diagnosis for TORCH Infections in women can help in proper management of these cases and prevent dreadful outcomes and pregnancy wastage. Rubella cases were 14 in our study, so incorporation of rubella immunization into the national immunization schedule, and to look into proper patient compliance is recommended.